Trends of and factors associated with access to residential toilets among the middle-aged and elderly in rural China from 2011 to 2018 - Qun Wang; Huiyuan Cao; Shuo Zhang (BMC, 2022)
Abstract Background At the global and country levels, several important sanitation improvement initiatives were launched in the last decade. This study aimed to explore the temporal trend of and factors associated with access to residential toilets among the middle-aged and elderly in rural China from 2011 to 2018. Methods This study used the 2011, 2013, 2015, and 2018 data of China Health and Retirement Longitudinal Study (CHARLS). CHARLS was conducted among adults aged ≥ 45 years in 28 provinces of China. We used descriptive statistics and logistic regressions for data analysis. Results We found that residential toilet coverage increased by about 6% among population aged ≥ 45 years in rural China from 2011 to 2018. The coverage of flushable toilets and toilets with seats among this sector of the population increased by more than 10% during this period. We also found that being female, higher levels of education, higher annual per capita household consumption, having running water in the residence, larger household size, and better health status were significantly associated with an increased likelihood of residential toilet ownership among population aged ≥ 45 years in rural China. Conclusions China made progress in sanitation improvement in rural areas from 2011 to 2018. However, considering the current coverage levels of residential toilets and the vulnerable subgroups who are more prone to toilet deprivation in rural areas, we suggest to the government to implement further targeted toilet improvement interventions to ensure universal coverage of sanitation facilities for the whole of the Chinese population.